Randomized, Prospective Comparison of Precut vs Surgeon-Dissected Grafts for Descemet Stripping Automated Endothelial Keratoplasty - Price, Marianne O.; Baig, Kashif M.; Brubaker, Jacob W.; Price, Francis W. (American journal of ophthalmology, 2008)
To determine whether eye bank predissected corneal grafts provide outcomes comparable to surgeon-dissected grafts for Descemet stripping automated endothelial keratoplasty (DSAEK). Randomized, prospective, double-masked clinical trial. Twenty pairs of donor corneas were harvested. One cornea from each pair was randomized to be precut at an eye bank for next-day use. The surgeon dissected the fellow cornea intraoperatively using a comparable microkeratome and protocol. The corneas were randomly assigned to 40 subjects having DSAEK at a single center. Subjects and evaluators were masked and statistical significance was assessed using the paired t test. Mean subject age was 71 ± 12 years and 90% had Fuchs dystrophy. Mean endothelial cell loss was 32% at six months and 34% at one year; the two groups did not differ by a statistically significant amount at either time point ( P = .10 and P = .79, respectively). Each group experienced two early dislocations (10%), and grafts were repositioned successfully with a second air bubble. At six months, 28 of 35 patients (80%) had best-corrected vision of 20/40 or better, excluding five patients (12%) with preexisting retinal problems ( P = .48). Both groups experienced a mild hyperopic shift ( P = .82), and neither had a statistically significant increase in mean refractive cylinder ( P = .63). Histology from one subject's eye postmortem demonstrated that endothelial cells had migrated over the exposed edge of the donor stroma a year after surgery. Eye bank precut tissue provided similar endothelial cell loss, visual and refractive outcomes, and detachment rates compared with surgeon-dissected tissue.